Maqroll y el imperio de la literatura Vol. 2 - Orejarena Torres, Jean; Ruiz Barrionuevo, Carmen; Klengel, Susanne; Alzate, Gastón Adolfo; Lefort, Michèle; Zamudio Tobar, Gladys; Rojas Arana, María Eugenia; Sánchez Borrero, Ana Milena; Bizzarri, Gabriele; D’Angelo, Biagio; Rodríguez Amaya, Fabio; Salinas Castaño, Alexander; et al. (Universidad Santiago de Cali, 2022)
Published